Overwash experiment on a sandy barrier - Matias, Ana (2019)
This paper uses results obtained from the large-scale BARDEX II experiment undertaken in the Delta flume to investigate the morphological response of a prototype sandy barrier to wave and tidal forcing during overwash conditions. Since overwash processes are known to control short-term barrier dynamics and long-term barrier migration, the development of a robust quantitative method to define the critical conditions leading to barrier overwash is important both for scientific and practical management purposes. The Overwash Potential (OP), defined as the difference between the wave runup and the barrier elevation is used to define the overwash threshold condition, and to predict the morphological outcome of a particular overwash event. When OP is negative, wave runup is lower than the barrier crest and insignificant morphological changes are noticed at the barrier crest. When OP is positive, overwash occurs because predicted runup elevation is higher than the barrier crest. When OP is close to zero, overtop is expected with limited intrusion of water across the top of the barrier crest. To make effective use of OP it is necessary to identify a reliable runup predictor. Twelve runup equations were tested for this purpose, and the results were compared with the ones obtained using data from BARDEX experiment on a gravel barrier. A most reliable approach for the determination of OP for sandy barrier was similar to gravel barrier overwash experiments, with runup predictions provided by the equation of Stockdon et al. [Stockdon, H.F., Holman, R.A., Howd, P.A.,Sallenger, A.H., 2006. Empirical parameterization of setup, swash, and runup. Coast. Eng., 53, 573-588]. This is striking, since different runup predictors would have been expected because beach slope, hydraulic conductivity, grain-size, amongst other factors, differ for both types of barriers. Nevertheless, the two main morphologic characteristics for the computation of OP are beach slope and the barrier crest elevation, both accounted for in the proposed equation. The use of OP values provides a practical means by which to identify potential coastal hazards associated with barrier overwash processes and is considered to have a range of practical coastal management applications.